46.1: Design of Full‐color Multi‐plane Augmented Reality Display with PSLC Scattering Shutters. (28th November 2018) - Liu, Shuxin; Li, Yan; Zhou, Pengcheng; Chen, Quanming; Li, Sida; Wang, Yunfen; Liu, Yueda; Su, Yikai
Abstract : A full‐color optical‐see‐through head mounted display (HMD) with polymer‐stabilized liquid crystal (PSLC) scattering shutters for augmented display was proposed. Three LEDs (RGB) and a DMD were used to achieve the quasi‐collimated projection image. Our system solves the accommodation‐vergence conflict with accurate depth cues.